2015
DOI: 10.1007/s10126-015-9654-8
|View full text |Cite
|
Sign up to set email alerts
|

Food Shortage Causes Differential Effects on Body Composition and Tissue-Specific Gene Expression in Salmon Modified for Increased Growth Hormone Production

Abstract: Growth hormone (GH) transgenic salmon possesses markedly increased metabolic rate, appetite, and feed conversion efficiency, as well as an increased ability to compete for food resources. Thus, the ability of GH-transgenic fish to withstand periods of food deprivation as occurs in nature is potentially different than that of nontransgenic fish. However, the physiological and genetic effects of transgenic GH production over long periods of food deprivation remain largely unknown. Here, GH-transgenic coho salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
2
3
0
Order By: Relevance
“…This discordance in results is intriguing and fosters speculation that the G6PASE gene expression changes observed may be strongly sensitive to experimental conditions and the nutritional status of the fish. Glucokinase was found to be elevated in the present study as well as in previous assessments that found enhanced potential for carbohydrate utilization in GH transgenic salmon [32,33]. LEPTIN also had large changes in expression between transgenotypes, but not between size classes.…”
Section: Gene Expression and Morphological Phenotypessupporting
confidence: 84%
See 1 more Smart Citation
“…This discordance in results is intriguing and fosters speculation that the G6PASE gene expression changes observed may be strongly sensitive to experimental conditions and the nutritional status of the fish. Glucokinase was found to be elevated in the present study as well as in previous assessments that found enhanced potential for carbohydrate utilization in GH transgenic salmon [32,33]. LEPTIN also had large changes in expression between transgenotypes, but not between size classes.…”
Section: Gene Expression and Morphological Phenotypessupporting
confidence: 84%
“…Previous measures of G6PASE1/2 have found differing results depending on whether fish were in a fed or food-deprived state. In the present study and that of Abernathy et al [32], fish were sampled while in a fed and growing state, and in both cases G6PASE mRNA levels were seen to be reduced in T relative to NT. In contrast, Panserat et al [33] analyzed fish in a food deprived state and did not detect a difference in mRNA level for G6PASE.…”
Section: Gene Expression and Morphological Phenotypessupporting
confidence: 54%
“…Significant feed deprivation has been shown to have a profound downregulating effect in genes involved in glycolysis [67]. Among others, glycolysis genes are differentially regulated between growth hormone transgenic and wild-type coho salmon during periods of long-term food shortage [68].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the neuroendocrine regulation of GH secretion in fish is multifactorial, with a balance of stimulatory and inhibitory neurohormones acting on pituitary somatotrophs. In addition, temperature (Picha et al, 2009;Zhou et al, 2015), season (Picha et al, 2009;Richmond, Jeanniard du Dot, Rosen, & Zinn, 2010), salinity (Moorman, Yamaguchi, Lerner, Grau, & Seale, 2016), starvation and refeeding (Pujante et al, 2015;Won & Borski, 2013), age (Li, Chen, Wong, & Lin, 2005;Richmond et al, 2010), gender (Ma et al, 2012), hormones (Linan-Cabello, Robles-Basto, & Mena-herrera, 2013;Wu, Li, Lin, & Li, 2012), diets (Li, Liu, Zhang, Ma, & Lin, 2013) and transgenosis (Abernathy et al, 2015;Leggatt et al, 2009;White, Volkoff, & Devlin, 2016) can also affect its distribution in tissues. Li et al (2013) found that cysteamine hydrochloride (CSH) feeding could induce the growth rate in Epinephelus coioides, and the luteinizing hormone-releasing hormone analogue (LHRH-A) could potentiate this growth stimulation effect.…”
Section: Introductionmentioning
confidence: 99%
“…() found that cysteamine hydrochloride (CSH) feeding could induce the growth rate in Epinephelus coioides , and the luteinizing hormone‐releasing hormone analogue (LHRH‐A) could potentiate this growth stimulation effect. GH transgenes is improved growth, feed intake and subsequent metabolic rates in fish; it also altered the utilization of dietary and stored carbohydrates, lipids and proteins as well as increased the ability for the fish to compete for food resources (Abernathy et al., ; Leggatt et al., ).…”
Section: Introductionmentioning
confidence: 99%